The linkages between photosynthesis, productivity, growth and biomass in lowland Amazonian forests. (20th March 2015) - Malhi, Yadvinder; Doughty, Christopher E.; Goldsmith, Gregory R.; Metcalfe, Daniel B.; Girardin, Cécile A. J.; Marthews, Toby R.; del Aguila‐Pasquel, Jhon; Aragão, Luiz E. O. C.; Araujo‐Murakami, Alejandro; Brando, Paulo; da Costa, Antonio C. L.; Silva‐Espejo, Javier E.; et al.
Abstract Understanding the relationship between photosynthesis, net primary productivity and growth in forest ecosystems is key to understanding how these ecosystems will respond to global anthropogenic change, yet the linkages among these components are rarely explored in detail. We provide the first comprehensive description of the productivity, respiration and carbon allocation of contrasting lowland Amazonian forests spanning gradients in seasonal water deficit and soil fertility. Using the largest data set assembled to date, ten sites in three countries all studied with a standardized methodology, we find that (i) gross primary productivity (GPP) has a simple relationship with seasonal water deficit, but that (ii) site‐to‐site variations in GPP have little power in explaining site‐to‐site spatial variations in net primary productivity (NPP) or growth because of concomitant changes in carbon use efficiency (CUE), and conversely, the woody growth rate of a tropical forest is a very poor proxy for its productivity. Moreover, (iii) spatial patterns of biomass are much more driven by patterns of residence times (i.e. tree mortality rates) than by spatial variation in productivity or tree growth. Current theory and models of tropical forest carbon cycling under projected scenarios of global atmospheric change can benefit from advancing beyond a focus on GPP. By improving our understanding of poorly understood processes such as CUE, NPP allocation and biomass turnover times, we can provide more complete and mechanistic approaches to linking climate and tropical forest carbon cycling.